NANOPARTÍCULAS MAGNÉTICAS: O COBALTO - Sargentelli, Vagner [UNESP]; Ferreira, Antonio P. [UNESP] (Ecletica Quimica, 2010)
The development of nanoparticles has been intensively pursued because of their technological importance. The magnetic nanoparticulate materials exhibit a series of interesting properties between which are mentioned the electrical, optical, magnetic and chemical properties. Magnetic nanostructures can be used in microelectronic and in medicine as in: magnetic memory storage, magnetic transport of biochemical complexes, magnetic resonance imaging, among others. The magnetic properties of nanoparticles there are very sensitive to its size and form. In this direction, many efforts they have been carried through with the intention of to control the form and distribution of the size of the nanoparticles. In the last few decades nanoparticles constituted by iron oxides had been studied. However, more recently, the focus of the researches has come back to others transitions metals. Amongst these, the cobalt comes being investigated due to its high magnetic susceptibility. In this context, the present article has the aim of to presents and to effect a comparative analysis of the more significant synthetic ways utilized in the present moment to obtain cobalt nanoparticles.
Keywords: Cobalt; Nanoparticles